2008
DOI: 10.1128/aac.01383-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of the Rx-01 Oxazolidinones against Hospital and Community Pathogens

Abstract: Rx-01_423 and Rx-01_667 are two members of the family of oxazolidinones that were designed using a combination of computational and medicinal chemistry and conventional biological techniques. The compounds have a two-to eightfold-improved potency over linezolid against serious gram-positive pathogens, including methicillin-resistant Staphylococcus aureus (MRSA), multidrug-resistant streptococci, and vancomycin-resistant enterococci. This enhanced potency extends to the coverage of linezolid-resistant gram-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 55 publications
(61 reference statements)
1
49
1
1
Order By: Relevance
“…In contrast, linezolid remains static intra- cellularly for at least 5 h and shows only a modest drop in CFU in broth at 20 mg/liter. These observations are consistent with the improved interaction of radezolid with its ribosomal target (25,53,61). In spite of this, however, the maximal effects reached at 24 h are similar for radezolid and linezolid at the highest concentrations tested (if the comparison is limited to linezolid-susceptible strains).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, linezolid remains static intra- cellularly for at least 5 h and shows only a modest drop in CFU in broth at 20 mg/liter. These observations are consistent with the improved interaction of radezolid with its ribosomal target (25,53,61). In spite of this, however, the maximal effects reached at 24 h are similar for radezolid and linezolid at the highest concentrations tested (if the comparison is limited to linezolid-susceptible strains).…”
Section: Discussionsupporting
confidence: 84%
“…In comparison to linezolid, it shows improved activity against a series of bacterial species capable of surviving intracellularly, such as Staphylococcus, Chlamydia, and Legionella species, and remains active against linezolid-resistant strains (25). In the companion paper, we showed that radezolid accumulates to about 12-fold-higher levels than linezolid in human THP-1 cells and localizes in lysosomes for about 40% of the total cell load, while the remainder is found in the cytosol (29).…”
mentioning
confidence: 87%
“…Once the optimal structural elements were determined, the activity of radezolid was assessed and it was found to bind with higher affinity to the ribosome than linezolid, which gave it enhanced antibacterial activity (2–8‐fold improvement over linezolid) against various Gram‐positive pathogens 45. Structure–activity studies of diverse oxazolidinones revealed that despite the presence of a C5 acylaminomethyl group in radezolid, it retains activity against the clinical cfr ‐positive CM05 strain of S. aureus with a minimal inhibitory concentration (MIC) value of 2 μg mL −1 , which is between those of tedizolid (0.5 μg mL −1 ) and linezolid (8 μg mL −1 ).…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…Radezolid (Rx-01_667, RX-1741; Rib-X Pharmaceuticals) (Fig. 3, compound 8) is a novel oxazolidinone with a broader spectrum of coverage and increased antibacterial activity against Gram-positive bacteria compared to those of linezolid (102). It offers the potential for improved antibacterial activity in that it is 2-fold more active in vitro than linezolid against staphylococci and 4-to 16-fold more potent against the streptococci and enterococci.…”
Section: Oxazolidinonesmentioning
confidence: 99%